Investigating the Role of Cloud-Based Information Sharing on Hospital Supply Chain Performance Using System Dynamics Approach (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Globally, increasing speed and quality and reducing expenses in the supply chain have been mentioned as companies` considered issues and important actions have been applied accordingly. Due to the rapid distribution, traditional approaches less respond to the chain expectations appropriately. Modern companies seek to find ways for optimizing their supply chains. As a profitable technology, cloud computing helps this optimization by providing substructures and software solutions for the overall supply chain. On the other hand, considering the recent years increase of services in the health management system, improving the supply chain has a high importance. Therefore, the current study evaluated the use of cloud-based information sharing and presented a dynamic model of the hospital supply chain based on the system dynamic approach as well as the analysis of related behaviors. The results of the investigation indicated that cloud-based information sharing model could improve the performance of supply chain components significantly.